Availability of Information and Communication Technology (ICT) Facilities and Strategies in Enhancing Teaching and Learning of Economics in Colleges of Education in North Central States, Nigeria - Musa, Okekwu Ate; Olunu, Njoku Uchechukwu (Researchparks Publishing, 2024)
The main purpose of this study was to find out the availability of Information and Communication Technology facilities and strategies for enhancing the teaching and learning of Economics in Colleges of Education in North Central States, Nigeria. The study was guided by two purposes, two research questions and two null hypotheses. The researcher adopted a descriptive survey research design. The study was carried out in the North Central States, Nigeria. The population comprised 140 Economics Lecturers and 87) NCE III students from selected Colleges of Education in the North Central States. A stratified sampling technique was used to draw a sample size of 114 NCE III students and the 140 lecturers were retained. Observation Checklist on Available ICT Facilities for Teaching and Learning Economics and a structured questionnaire were used for data collection. The reliability of the instrument was ascertained using Cronbach Alpha and an overall reliability coefficient of .97 was ascertained. Frequency, percentage, mean and standard deviation were used to answer research questions while an independent sampled t-test was used to test null hypotheses at a 0.05 level of significance. The Findings of this study revealed lecturers and students agreed that computer-assisted instruction, computer-aided design, performance monitoring, problem-solving, video lectures and use of individualized instruction were used to a high extent as ICT strategies for enhancing teaching and learning in the college of education. Computer-assisted instruction and computer-aided instruction have been found to be useful in teaching and learning Economics content in colleges of education especially where students are equipped with required skills. Therefore, to improve the teaching of Economics in Colleges of Education in North Central State, Nigeria, it is imperative to establish robust ICT infrastructure and upgrade existing facilities.